LITERACY AND NUMERATION INTEGRATED IN PHYSICAL EDUCATION LEARNING THROUGH THE PROGRAM EDU-FUN-HEALTH - Atho'illah, Muhammad; Rizki Apriliyanto; Topo Yono (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
Numeracy literacy is very important as a basic competency for students to prepare them to face challenges in real life. This study aims to improve students' numeracy literacy through the EDU-FUN-HEALTH program. This type of research is classroom action research with a two-cycle model. The subjects of the study were 16 fifth grade students at Padomasan 03 Elementary School, Padomasan District, Jember Regency. The research instruments included observation, skill tests, and knowledge tests. Data were analyzed using percentages, with the achievement level set at 75%. The results showed that the use of game modifications succeeded in improving student learning outcomes in manipulative motor skills. The percentage of learning completion increased from 62.5% in cycle 1 to 87.5% in cycle 2. In addition, there was also an increase in numeracy literacy, which changed from the Good category to Very Good between cycle 1 and cycle 2. Regency.